Prehospital Transdermal Glyceryl Trinitrate for Ultra-Acute Intracerebral Hemorrhage: Data From the RIGHT-2 Trial. Issue 11 (November 2019) - Bath, Philip M.; Woodhouse, Lisa J.; Krishnan, Kailash; Appleton, Jason P.; Anderson, Craig S.; Berge, Eivind; Cala, Lesley; Dixon, Mark; England, Timothy J.; Godolphin, Peter J.; Hepburn, Trish; Mair, Grant; et al.
Abstract : Background and Purpose—: Pilot trials suggest that glyceryl trinitrate (GTN; nitroglycerin) may improve outcome when administered early after stroke onset. Methods—: We undertook a multicentre, paramedic-delivered, ambulance-based, prospective randomized, sham-controlled, blinded-end point trial in adults with presumed stroke within 4 hours of ictus. Participants received transdermal GTN (5 mg) or a sham dressing (1:1) in the ambulance and then daily for three days in hospital. The primary outcome was the 7-level modified Rankin Scale at 90 days assessed by central telephone treatment-blinded follow-up. This prespecified subgroup analysis focuses on participants with an intracerebral hemorrhage as their index event. Analyses are intention-to-treat. Results—: Of 1149 participants with presumed stroke, 145 (13%; GTN, 74; sham, 71) had an intracerebral hemorrhage: time from onset to randomization median, 74 minutes (interquartile range, 45–110). By admission to hospital, blood pressure tended to be lower with GTN as compared with sham: mean, 4.4/3.5 mm Hg. The modified Rankin Scale score at 90 days was nonsignificantly higher in the GTN group: adjusted common odds ratio for poor outcome, 1.87 (95% CI, 0.98–3.57). A prespecified global analysis of 5 clinical outcomes (dependency, disability, cognition, quality of life, and mood) was worse with GTN; Mann-Whitney difference, 0.18 (95% CI, 0.01–0.35; Wei-Lachin test). GTN was associated with larger hematoma and growth, and more mass effect and midline shift on neuroimaging, and altered use of hospital resources. Death in hospital but not at day 90 was increased with GTN. There were no significant between-group differences in serious adverse events. Conclusions—: Prehospital treatment with GTN worsened outcomes in patients with intracerebral hemorrhage. Since these results could relate to the play of chance, confounding, or a true effect of GTN, further randomized evidence on the use of vasodilators in ultra-acute intracerebral hemorrhage is needed. Clinical Trial Registration—: URL: http://www.controlled-trials.com . Unique identifier: ISRCTN26986053. Abstract : Supplemental Digital Content is available in the text.